Analisis dan Perencanaan Sistem Drainase Di Jl. Raden Gunawan 2 Kecamatan Rajabasa Bandar Lampung - Syah, Ismawan Dewan; Arifaini, Nur; Purwadi, Ofik Taupik (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
The occurrence of floods at Raden Gunawan 2 street, Rajabasa district, Bandar Lampung was caused by the inability of existing drainage channels to accommodate direct run-off discharge and blockage of drainage channels by garbage.Hydrological analysis was performed by using the maximum rainfall data within the last 10 years, then, parameter calculation were performed to calculate the discharge plan using rational method. The wide-scale of watershed is 0.77308 km2 and the drainage coefficient is 0.5132. The hydraulic analysis was conducted to calculate the drainage channel discharge capacity using continuity formula and Manning formula, after that, suitable systems and dimensions were planned.Based on the results of the research, the suitable rain distribution is Log Pearson III Distribution which obtained rainfall value of plan for the 5-year rework time of 109,016 mm and the amount of the biggest discharge at joint segment between primary channel and Kemiling area is 2,8336 m3 / sec. Then, flood heights were found in the research area as high as 10-30 cm, because the existing dimensions were not able to accommodate the discharge plan. Thus, suitable channel dimensions are planned using U-Ditch shaped sections with U100 / 100, U150 / 150, U150 / 250 and U250 / 250 sizes. So, the discharge plan (Qr) is smaller than the discharge channel (Qs). Keywords: drainage, hydrology, hydraulics, distribution.